kohtaus Kansallisteatterin "Elina surma" -näytelmästä - Atelier Apollo
sisällön kuvaus: vasemmalta: Aleksis Rautio, Katri Rautio, Knut Weckman, Ida Aalberg, Olga Poppius, Mimmy Leino, Benjamin Leino ja Axel Ahlberg
Keywords: teatterit; näyttelijät; näyttämöt; rooliasut; lavasteet; taljat (nahka); Aalberg, Ida; Ahlberg, Axel; Leino, Benjamin; Leino, Mimmy; Poppius, Olga; Rautio, Aleksis; Rautio, Katri; Weckman, Knut; Suomi, Helsinki, Helsinki